The making of politics and trained intelligence in the Near East: Robert College of Istanbul - ERKEN, ALİ (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2016)
This article examines the role of Robert College in Turkish-American relations in the early decades of the Turkish Republic. Relying on recently discovered archival sources and biographical accounts it explores political and educational networks between the United States and Turkey. Robert College, founded in 1863, was the first American College established abroad. It was, however, more than an educational institution; the College teaching staff acted as diplomatic and cultural correspondents for both countries. The trust the College staff earned among the Turkish elite during the First World War continued in the early years of Republic. This relationship turned into a more lucrative collaboration during the early periods of the Cold War. The story of Robert College in Turkey demonstrates the impact of trained intelligence on political relations between the two countries.
Keywords: elite networks; political networks; modern Turkish history; political history; philanthropy